FORMATION OF MATHEMATICAL COMPETENCE AT FUTURE PROGRAMMERS MEANS OF ICT (Journal of Information Technologies in Education (ITE), 2015)
In article questions of formation of mathematical competence at future programmers by means of introduction in process of training of mathematical disciplines of pedagogical software are considered, средств, involving the use of communicative and information technologies. In particular, the problem of the use disclosed in the course of teaching the course of analytical geometry software pedagogical tools «Analytic geometry» developed by the Laboratory of Information Technologies of Kherson State University, led by professor Lvov M.S. The main attention is paid to the problems of formation of mathematical competence, which is an integral part of training for future programmers. We consider the basic principles developed by pedagogical tools that reflect the specific training under the competence approach in education. The basic directions of the use of ICT for the organization of the learning process for the purpose of formation of mathematical knowledge and skills, as well as methodical features use components developed software modules developed software tools in the study of the course of analytical geometry during the lectures and practical classes, as well as for the organization of independent work of students,control of received knowledge and skills.
Keywords: mathematical competence; pedagogical software